An efficient siRNA‐mediated gene silencing in primary human monocytes, dendritic cells and macrophages. Issue 8 (3rd June 2014) - Troegeler, Anthony; Lastrucci, Claire; Duval, Carine; Tanne, Antoine; Cougoule, Céline; Maridonneau‐Parini, Isabelle; Neyrolles, Olivier; Lugo‐Villarino, Geanncarlo
Abstract : Mononuclear phagocytes (MP) comprise monocytes, macrophages (MΦ) and dendritic cells (DC), including their lineage‐committed progenitors, which together have an eminent role in health and disease. Lipid‐based siRNA‐mediated gene inactivation is an established approach to investigate gene function in MP cells. However, although there are few protocols dedicated for siRNA‐mediated gene inactivation in primary human DC and MΦ, there are none available for primary human monocytes. Moreover, there is no available method to perform comparative studies of a siRNA‐mediated gene silencing in primary monocytes and other MP cells. Here, we describe a protocol optimized for the lipid‐based delivery of siRNA to perform gene silencing in primary human blood monocytes, which is applicable to DCs, and differs from the classical route of siRNA delivery into MΦs. Along with this protocol, we provide a comparative analysis of how monocytes, DC and MΦ are efficiently transfected with the target siRNA without affecting cell viability, resulting in strong gene knockdown efficiency, including the simultaneous inactivation of two genes. Moreover, siRNA delivery does not affect classical functions in MP such as differentiation, phagocytosis and migration, demonstrating that this protocol does not induce non‐specific major alterations in these cells. As a proof‐of‐principle, a functional analysis of hematopoietic cell kinase (Hck) shows for the first time that this kinase regulates the protease‐dependent migration mode in human monocytes. Collectively, this protocol enables efficient gene inactivation in primary MP, suggesting a wide spectrum of applications such as siRNA‐based high‐throughput screening, which could ultimately improve our knowledge about MP biology.